THE ROLE OF ENGINEERING GRAPHICS IN PROJECT ACTIVITIES - Yerpolat Allanyazov Bakhavedinovich (European Science Publishing, 2024)
Engineering graphics are an integral part of the engineering process. It allows engineers to visualize their ideas and present them to other project participants. It is a key tool for communication and coordination during design and production, as well as in the process of collaboration between engineers, architects and builders.
Keywords: Engineering graphics, engineers, visualize, project, communication, design, information.